Covariant density functional NL3, ten years after - Karatzikos, S.; Lalazissis, G. A.; Fossion, R.; Peña-Arteaga, D.; Ring, P. (HNPS Advances in Nuclear Physics, 2020)
We propose a modification of the effective force NL3, which presents the very succesful parameterization for the Lagrangian of the Relativistic Mean Field (RMF) theory. The new effective force with the name NL3* has phenomenological para- meters. It improves the ground state properties of many nuclei and simultaneously provides an excellent description of excited states with collective character in sphe- rical and axially deformed nuclei.